GERD-related chronic cough: Possible mechanism, diagnosis and treatment - Wu, Jiankang; Ma, Yiming; Chen, Yan (Frontiers in Physiology, 2022)
GERD, or gastroesophageal reflux disease, is a prevalent medical condition that affects millions of individuals throughout the world. Chronic cough is often caused by GERD, and chronic cough caused by GER is defined as GERD-related chronic cough (GERC). It is still unclear what the underlying molecular mechanism behind GERC is. Reflux theory, reflex theory, airway allergies, and the novel mechanism of esophageal motility disorders are all assumed to be linked to GERC. Multichannel intraluminal impedance combined with pH monitoring remains the gold standard for the diagnosis of GERC, but is not well tolerated by patients due to its invasive nature. Recent discoveries of new impedance markers and new techniques (mucosal impedance testing, salivary pepsin, real-time MRI and narrow band imaging) show promises in the diagnosis of GERD, but the role in GERC needs further investigation. Advances in pharmacological treatment include potassium-competitive acid blockers and neuromodulators (such as Baclofen and Gabapentin), prokinetics and herbal medicines, as well as non-pharmacological treatments (such as lifestyle changes and respiratory exercises). More options have been provided for the treatment of GERC other than acid suppression therapy and anti-reflux surgery. In this review, we attempt to review recent advances in GERC mechanism, diagnosis, and subsequent treatment options, so as to provide guidance for management of GERC.